SOCIOCULTURAL FUNCTIONS OF HIGHER EDUCATION IN INFORMATION SOCIETY - Bronnikova, Larysa (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Education plays an important role in the life of society, occupies a special place in the cultural system. Therefore, education is a subject of philosophical study too. The content, goals and functions of higher education are determined by the needs of society. It is necessary to comprehend what is happening with higher education in the information age. The aim and tasks. The article examines the influence of various factors on the content of the socio-cultural functions of higher education. It is necessary to determine the guidelines for a new paradigm of higher education in the information society. Research methods. The methodological basis of this study is a complex of philosophical and general scientific methods. The sociocultural, systemic and synergetic approaches were also used. In the light of the synergetic approach, culture is viewed as a self-developing system. Synergetics helps to comprehend the non-linear processes that occur both in the education system and its relations with the sociocultural environment. Research results. Education is a part of society and culture. Sometimes society makes claims to the education sector. But gradually the contradictions are resolved. If the country is in a state of permanent crisis, it penetratesinto all spheres of human life. Education is both conservative and innovative. The stability of the education sector has developed historically – since the days of medieval schools and universities. At the same time, each era adds new ideas and pedagogical technologies to education. Ukraine became an independent state 30 years ago. Political changes have significantly influenced the institution of education. Summarizing all educational transformations, we can say that they were unsystematic, even chaotic, and depended on the next team that came to power in our country. Another reason for significant changes in the education system was the transition to an information society and the need to train appropriate specialists for all spheres of life. The number of universities and students has increased in Ukraine, but for effective changes in the field of higher education its a new model, a paradigm is needed. Discussion. In the academic publications of Ukraine, there is a lack of clarity and fragmentation in the definition of both the general state of the higher education system and the prospects for its renewal.Соnclusion.Currently, there is a search and application of new educational technologies, a combination of traditional and innovative approaches to meet the socio-cultural needs of the information age.